A fish-based biotic integrity index for assessment of lowland streams in southeastern Brazil - Casatti, Lilian [UNESP]; Ferreira, Cristiane P. [UNESP]; Langeani, Francisco [UNESP] (Springer, 2009)
This study was carried out to develop and apply a fish-based biotic integrity index to assess lowland streams in a highly deforested region of the Upper Parana River basin. Fifty-six first-order segments were randomly selected for environmental and fish evaluation. Because previous analysis had identified the main type of effect on the streams of the region as physical habitat degradation, 22 qualitatively biological attributes were selected and tested over a physical condition gradient between reference and degraded sites. Sensitivity and redundancy of each attribute revealed that five metrics were adequate for discriminating higher quality from degraded sites. of the fifty-six streams assessed, one (2%) was classified as good, four (7%) as fair, ten (18%) as poor, and forty-one (73%) as very poor, indicating that, on a regional scale, many aspects of biological integrity are altered, indicative of serious degradation. Considering that first-order segments amount to 11,000 km in total, it is noticeable that 10,000 km of the stream segments have no more than half of the expected conditions, indicative of poor or very poor biotic integrity conditions. Possible strategies of mitigating this scenario are discussed.
Keywords: Ichthyofauna; Habitat quality; Conservation; IBI; Biological monitoring